The influence of human resource competence and work ethic on the professionalism of employees at the Large Drug and Food Inspection Center in Palembang - Maliah, Maliah; Hidayat, Tamsir; Hendri, Edduar; Novalia, Nurkardina (Goodwood Publishing, 2025)
Purpose: This study aimed to determine the effect of human resource competence and work ethic, both partially and simultaneously, on the professionalism of employees at the Palembang Food and Drug Administration. Methodology/approach: The population consisted of 106 employees, including 83 Civil Servants (PNS) and 23 Non-Civil Servants (PPNPN). The sample comprised 83 Civil Servants (PNS) selected using purposive sampling. Data were analyzed using SPSS version 20 with validity, reliability, normality, heteroscedasticity, multicollinearity tests, multiple linear regression analysis, coefficient of determination (R2), t-test, and F-test. Results: The t-test results show that human resource competence has a positive and significant effect on professionalism, while work ethic has a less significant negative effect. The F-test indicates that both human resource competence and work ethic significantly affect employee professionalism at the Palembang Food and Drug Examination Center. Conclusions: Human resource competence positively influences employee professionalism, whereas work ethics have a less significant negative effect. Together, these two factors significantly contribute to professionalism at the center. Limitations: The study was limited to Civil Servants (PNS) at the Palembang Food and Drug Administration and may not apply to other institutions or employee types. Contribution: This study contributes to the understanding of how human resource competence and work ethic influence employee professionalism, particularly in public sector institutions such as the Food and Drug Administration.